(untitled) (Bangladesh Journal of Medical Science, 2025)
Background Timeliness and sufficiency of the emergency medical services within the first hours of the disease are among the main factors defining prognosis of the patients with the acute myocardial infarction (AMI). Aim The purpose of this study is assessment of attendance and hospitalization timeliness by the emergency medical services (EMS) on fatality rate of the patients with the acute myocardial infarction. Materials and methods. The patients (n = 531) with the signs of the acute myocardial ischemia were included in the study with the various outcomes at prehospital phase of the emergency medical services. Statistical treatment of the material has been carried out using absolute and relative values. Outcomes. Untimely arrival of the emergency medical services physician to the patient from the moment of call receipt, AMI diagnosis and earlier hospital admission after the first examination of the EMS physician exert a great influence over probability of mortality due to acute myocardial infarction at prehospital phase. Result The specific weight of the patients attended by the EMS physicians within the range of 0-29 minutes has increased by 19.4% after implementation of the program of the AMI’s register, the number of undiagnosed AMI cases by the EMS physicians has reduced by 16.4%, and the specific weight of the hospitalized after the first examination by the EMS physicians has increased by 7.2%. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 145-154